Sistem Demokrasi (Kebebasan Berpendapat) Masyarakat Di Indonesia Dalam Perspektif Sila Ke-4 - Jekson Saragih; Yakobus Ndano (Pusat Riset dan Inovasi Nasional, 2024)
The Indonesian nation is a nation that adheres to the Pancasila philosophy, therefore every value in the Pancasila principles must be applied in national and state life. As the 4th principle of Pancasila states